Trajetórias de formação de educadores sociais nos Centros Pop da Grande Vitória - Silva, Samuel Coelho da (2018)
This dissertation had as general objective to investigate how the formation and the trajectory of the social educators to the development of activities directed to the homeless people attended in the Pop Centers (Special Reference Center for Homeless People) of the Metropolitan Region of the Greater Vitória are constituted. In order to do so, more specifically, we set out the objectives of: understanding the process of formation of social educators who work in the multidisciplinary team of pop centers of Greater Vitória, before joining and staff and during their stay; analyze the experiences that led these employees to work with the homeless people. This work is justified by the need to understand the training and qualification of the group of social educators who work at the Pop Center, because, from the unfolding of the research, we can see if the training policy proposed in the documents and its principles and guidelines contribute to the process of daily intervention. The research is characterized methodologically as qualitative in function of the elements used to subsidize the question from the social educators. In order to carry out this study, we articulated the documentary research, which consisted of the collection and analysis of documents related to the assistance policies that support the implementation of the service and the fieldwork, with application of the instruments used for data production, such as observation script, the questionnaire and the semi-structured interview script. The choice of these instruments was necessary to understand the dynamics of the research scenario, in order to observe the ways in which social assistance policies materialized in daily life, especially in the training of social educators aimed at attending to the population living in the street. In the description and analysis of the data, it was possible to verify the relevance of the social educators in the interventions and in the implementation of the social assistance policy offered by the Pop Centers. We also point out the possibility of corporal practices, even in a specific way, to be part of the activity list offered by these professionals, opening space for the inclusion of Physical Education teachers in the multidisciplinary team of the Pop Center adding to the implementation of social assistance policies. The majority of educators, even though they did not have specific training to work in the area under investigation, demonstrated their commitment to the activities under their responsibility.